PERSEPSI ANGGOTA KELOMPOK WANITA TANI TERHADAP PROGRAM MODEL KAWASAN RUMAH PANGAN LESTARI (M-KRPL) DI KABUPATEN SIAK - Siti Nur Rohimah; Rosnita '; Kausar ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research to know internal and external characteristic of KWT women farmers group, to know perception of KWT members toward model sustainable region food home (M -KRPL) program, to know relationship between   internal and external characteristic toward  perception of the KWT members, and also to know impact of the assembling successed M-KRPL program. This research was conducted in Tualang Village Tualang District Siak and SialangBaru Village LubukDalam District Siak Regency. The method used of this research was descriptive method. This research would be using sampling technic and the numbers of sample was taken by KWT members and using aquestionnaire as instrument measure data. Level of participation members measured using ordinal scale, while to answer internal and external characteristic relationship toward perception of KWT members usingKorelasiSpearman. The result figure out:(1) Perception of participation toward internal and external characteristic was categorized as “good”: (2) perception of KWT members toward M-KRPL program were categorized as “good” Siak regency: (3) Internal characteristic relationship level of education and how be longer werejoined perception of the relative profit contained as “real relationship” while external characteristic on intensity of extension worker with the perception relative profit on “real relationship“: (4) Impact of successful toward KWT members in Siak regency was categorized as “good “ on the strength of increasing expectation food model (PPH), manufacture increasing, (kinds of communities, total and quality) household expending economical. Keywords: Model Sustainable Region Food Home (M -KRPL) program, Women Farmers Group (KWT), perception